Effect of grain type in supplements and supplementation frequency on the performance of beef cows grazing winter range - R.C. Cochran; J.L. Beaty; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1994)
One hundred twenty, pregnant, Angus x Hereford cows (1111 lb) grazing dormant bluestem range were used to evaluate whether the effect of altered frequency of supplementation on cow performance depended on the grain type in the supplement. Two supplementation frequencies (daily and three times weekly) and two grain types in the supplements (sorghum grain or corn) were evaluated. Both supplements contained 21% CP and were fed to provide 32.6 lb DM/week. Interactions were not significant. Winter weight loss through calving was greater (P#.02) for the cows supplemented three times weekly, although the magnitude of the effect was not large. Use of different grain types in the supplements did not significantly affect most performance variables.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Beef cattle; Frequency; Supplements